Analysis of criteria for choosing drug treatment strategies in allergic rhinitis - Grzegorzewski, Damian; Sobczak, Marharyta; Tołkacz, Michał; Pawliczak, Rafał (Frontiers in Pharmacology, 2024)
Background: Allergic rhinitis is the most common type of rhinitis, treatment of which relies on relief of symptoms. Therefore, we aimed to assess the criteria, which influence doctors’ decision-making in the process of drug selection for the treatment of allergic rhinitis based on quantitative, qualitative and cost analysis Methods: We conducted a survey study with participation of 300 allergists. An in-house made questionnaire was presented during the computer assisted telephone interview (CATI) according to the standard procedures. Contingency table underwent statistical analysis using the Chi-Square Test with Cramer's v. Results were considered statistically significant at p<0.05. Results: Our analyses showed that doctors most often prescribe intranasal glucocorticoids and oral antihistamines to treat allergic rhinitis in patients of all ages. The most common factor, which affect the decision making related to AR treatment was efficiency of drug. We found the significant relationship between factors and main workplace (X-squared = 122.81, df = 90, p-value = 0.0123, Cramer’s V = 0.1787216), as well as voivodship of main workplace (X-squared = 440.75, df = 270, p-value = 2.378e-10, Cramer’s V = 0.1954731). In our study, respondents claimed that patients are willing to pay monthly 31-50 PLN (~ €7- €11) for treatment of allergic rhinitis with mild and moderate form; while 51-100 PLN (~ €11 - €22) in severe form. Conclusion: Our study confirms that management of AR should be focused on the patient. One of the most important factors in choosing a drug is its effectiveness. Moreover, an important factor in the effective treatment of AR is the financial issue, as our analysis shows, AR treatment costs can be a significant burden, especially for less wealthy citizens in Poland.